Assessment on the circular economy for waste minimization in the construction industry / Dr Mohd Reza Esa, Wan Azlan Shah Eddie Shah Edward and Anthony Halog - Esa, Mohd Reza; Eddie Shah Edward, Wan Azlan Shah; Halog, Anthony (UiTM Press, 2021)
The movement towards sustainability and resiliency has become a central talking point for the Malaysian government. Waste that is immeasurably generated from the construction activities should be appropriately managed to preserve the environment. This study was conducted to assess the level of knowledge about the concept of Circular Economy (CE) as an approach for waste minimization via a survey questionnaire sent to the G7 contractors in the Klang Valley area. The ultimate version of the questionnaire consisted of 38 questions, and it was sent to 360 targeted G7 contractors. 135 questionnaires were returned with a response rate of 37.5%. The results reveal that most of the contractors were knowledgeable about the potential of the CE concept as an approach for waste minimization. Environmental sustainability would be attained when the CE concept is used to minimize the waste generated from the construction activities. The integration of adaptative reused is found to be suitable to enhance the implementation of the CE concept. The results revealed considerable potential for the CE concept to be used as a waste minimization approach in the construction industry. In this sense, the enhancement of the CE concept implementation throughout the construction cycle could set up a direction for future research.